Overview of tokamak turbulence stabilization by fast ions. (1st March 2023) - Citrin, J; Mantica, P
Abstract: In recent years tokamak experiments and modelling have increasingly indicated that the interaction between suprathermal (fast) ions and thermal plasma can lead to a reduction of turbulence and an improvement of confinement. The regimes in which this stabilization occurs are relevant to burning plasmas, and their understanding will inform reactor scenario optimization. This review summarizes observations, simulations, theoretical understanding, and open questions on this emerging topic.